2021
DOI: 10.1093/jmammal/gyaa163
|View full text |Cite
|
Sign up to set email alerts
|

Potential use of a magnetic compass during long-distance dispersal in a subterranean rodent

Abstract: Geomagnetic sensitivity is present in a variety of vertebrates, but only recently has attention focused on subterranean mammals. We report the potential use of a magnetic compass in wild Damaraland mole-rats (Fukomys damarensis) during dispersal at two sites in the Kalahari region of South Africa. When the distance traveled was greater than 250 m, males and females dispersed in opposite directions and females preferentially chose a predominantly northeastern direction. This directional choice likely is due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Since these and other dispersals cross the territories of multiple other established colonies, it is likely that these may represent aboveground dispersal events. Finn [ 57 ] hypothesized that dispersal distances greater than 250 m are likely to represent aboveground dispersal in Damaraland mole-rats, due to the high energetic costs associated with digging. Long-distance dispersal can thus be risky, exposing individuals to predation, aggressive interactions with conspecifics, loss of body condition and stress [ 31 , 39 , 58 ], while also trading off against cooperative contributions that they might otherwise have made within their natal group [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since these and other dispersals cross the territories of multiple other established colonies, it is likely that these may represent aboveground dispersal events. Finn [ 57 ] hypothesized that dispersal distances greater than 250 m are likely to represent aboveground dispersal in Damaraland mole-rats, due to the high energetic costs associated with digging. Long-distance dispersal can thus be risky, exposing individuals to predation, aggressive interactions with conspecifics, loss of body condition and stress [ 31 , 39 , 58 ], while also trading off against cooperative contributions that they might otherwise have made within their natal group [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…76%) taking on long-distance dispersal (> 250 m) than males (27 out of 47 male dispersers, i.e. 57%), although the number of male dispersers (47 individuals) was still higher overall than females (41 individuals) [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Birds may rely on a few features of magnetic fields including intensity (strength of the magnetic field), inclination (the angle between the magnetic field and earth surface), direction (polarity), and declination (the difference between true north and magnetic north) (Wallraff, 2005;Wiltschko, 2005, 2015;Mouritsen, 2018). While much of the research on magnetic compasses has been done in birds, there is growing evidence that mammals, specifically rodents and bats, also possess a magnetic compass (Holland et al, 2006(Holland et al, , 2010Oliveriusová et al, 2012Oliveriusová et al, , 2014Finn, 2021). Some large terrestrial mammals can spontaneously align their bodies with magnetic fields (Begall et al, 2013;Obleser et al, 2016;Painter et al, 2016;Červený et al, 2017), but it is unclear if they use an established magnetic compass for navigation.…”
Section: Magnetic Compassmentioning
confidence: 99%
“…Indeed, very few individuals within a Damaraland mole-rat populations breed at some point in their lives (<8%; Jarvis and Bennett, 1993;Torrents-Ticó et al, 2018;Mynhardt et al, 2021;Thorley et al, 2021). Previous field studies of social mole-rats have shown that when individuals disperse, they frequently do so alone and rarely in coalitions (Jarvis and Bennett, 1993;Torrents-Ticó et al, 2018), and evidence suggests that dispersal occurs both above and below ground (Hazell et al, 2000;Bray et al, 2012;Patzenhauerová et al, 2013;Finn, 2021). By blocking themselves off into a section of the natal burrow, individuals can form a new territory via "territory budding" (Jarvis and Bennett, 1993;Lövy et al, 2013;Mynhardt et al, 2021).…”
Section: Introductionmentioning
confidence: 99%